Mayflies of the genus Nonnullidens Grant & Peters 1993 (Ephemeroptera: Leptophlebiidae) from New Guinea - Kluge, Nikita J. (Zootaxa, 2013)
In light of the discovery of four new species of Leptophlebiidae (Ephemeroptera) from the Indonesian part of New Guinea, the generic name Barba Grant & Peters 1993 syn.n. is regarded here to be a junior synonym of Nonnullidens Grant & Peters 1993. Nonnullidens variegatus sp. n., N. niger sp. n. and N. reductus sp. n. are described from larvae, subimagoes and imagoes, with the stages associated by rearing. Nonnullidens depapricus sp. n. is described from an immature male larva of the last instar. Nonnullidens mariae comb.n. formerly known only from eastern New Guinea, is reported from the Baliem Valley.